2022
DOI: 10.1126/sciadv.abn4426
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic network of intermolecular interactions in metal-organic frameworks functionalized by molecular machines

Abstract: Molecular machines enable external control of structural and dynamic phenomena at the atomic level. To efficiently transfer their tunable properties into designated functionalities, a detailed understanding of the impact of molecular embedding is needed. In particular, a comprehensive insight is fundamental to design hierarchical multifunctional systems that are inspired by biological cells. Here, we applied an on-the-fly trained force field to perform atomistic simulations of a systematically modified rotaxan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…The existence of a sharp, intense diffraction peak at 5.1° indicated the high crystallinity of COF-I, which is representative of the (100) plane in this new hexagonal olefin-linked 2D COF. To deduce the structure and the configuration of the layers in COF-I, we performed atomistic simulations (Figure b). Following the previously introduced parametrization approach and studies and utilizing the Tinker code, we parametrized a force field using quantum-mechanical (QM) reference data (BLYP+D3/cc-pVDZ). By using these interatomic potentials to optimize both the geometry of the COF and the cell parameters and systematically varying the interlayer arrangement, we could discriminate the three-dimensional structures energetically. These atomistic simulations revealed that, for the solvent-free structure, the energetically most preferred structure is a highly dense slipped layer stacking, which increases the interaction between the layers.…”
Section: Resultsmentioning
confidence: 99%
“…The existence of a sharp, intense diffraction peak at 5.1° indicated the high crystallinity of COF-I, which is representative of the (100) plane in this new hexagonal olefin-linked 2D COF. To deduce the structure and the configuration of the layers in COF-I, we performed atomistic simulations (Figure b). Following the previously introduced parametrization approach and studies and utilizing the Tinker code, we parametrized a force field using quantum-mechanical (QM) reference data (BLYP+D3/cc-pVDZ). By using these interatomic potentials to optimize both the geometry of the COF and the cell parameters and systematically varying the interlayer arrangement, we could discriminate the three-dimensional structures energetically. These atomistic simulations revealed that, for the solvent-free structure, the energetically most preferred structure is a highly dense slipped layer stacking, which increases the interaction between the layers.…”
Section: Resultsmentioning
confidence: 99%
“…While atomic simulations are indispensable for providing static information and translation rates within hierarchical multifunctional systems at the equilibrium stage, 75 they may fall short when addressing phase transitions in self-assembly that extend beyond equilibrium. In such cases, DPD simulations come to the fore.…”
Section: Multiscale Modeling In Molecular Machinesmentioning
confidence: 99%
“…In contrast, Kolodzeiski et al. investigated cooperative shuttling in a rotaxane-based MOF and the collective behavior that can arise from such a complex system 75 . However, among the most intriguing and thought-after properties is directed activated diffusion (i.e., pumping) via the rotational motion of molecular motors in porous frameworks.…”
Section: Functional Dynamics Across Length and Time Scalesmentioning
confidence: 99%